Diversity of Mangrove In Gedangan Village Purwodadi Subdistrict Purworejo Regency Central Java - Slamet Mardiyanto Rahayu; Syuhriatin Syuhriatin; Wiryanto Wiryanto (Jurnal Ilmu Alam dan Lingkungan, 2018)
This research aims to know diversity of mangrove in Gedangan Village, Purwodadi Subdistrict, Purworejo Regency, Central Java. This research conducted on June-September 2016 with purposive sampling methods with three station. Based on the results of the research are nine mangrove species found are: Rhizophora mucronata, Sonneratia alba, Nypa fruticans, Hibiscus tiliaceus, Ipomoea pescaprae, Acanthus ilicifolius, Gymnanthera paludosa, Wedelia biflora, and Scirpus sp. Diversity of tree mangrove are low (H’ station 2=0,95 and H’ station 3= 0,15). Diversity of sapling mangrove are low with H’ in station 1, 2, and 3 are 0,2; 0,68; dan 0,08. And diversity of mangrove seedling and lower plants are medium with H’ in station 1, 2, and 3 are 1,17; 1,56; and 1,48. Environment condition in all station is relatively good to support live of mangrove plant.That is temperature  28-30°C, pH 7-8, DO 4,0-6,5 mg/l, salinity 6-9 ppt, and sandy mud substrat.